Developing a staff development framework for nursing homes in Malaysia: content analysis based on expert interviews - Hasif Rafidee Hasbollah; Nurul Ashykin Abd Aziz; Nur A’mirah Mohd Yaziz; Mohd Shafhuan Yusran; Mohd Firdaus Mohd Nasir; Siti Nabilah Mohd Rosdi (2016)
This paper aims to develop a Staff Development Framework for Nursing Homes (SDFNH) to improve staff and organizational effectiveness in nursing homes in Malaysia. Expert Interviews with five nursing homes were conducted via purposive sampling and analyzed using Content Analysis. The results indicate that the SDF-NH integrates: (a) people, who are qualified staff, and the development of attitude, skills, knowledge (ASK), and performance for the effectiveness of service delivery; (b) program, which includes training and motivation, practical courses, and job rotation as training; (c) process, which is the strategy of continuous improvement of people and program in the nursing homes; (d) funds, which are government financial support to assist the NHs; and (e) rewards, which are one of the incentives to retain the staff’s services.